2019
DOI: 10.1002/iub.2135
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PID1 reduces high density lipoprotein level and functionality in swine

Abstract: Phosphotyrosine interaction domain 1 (PID1), a protein with a phosphotyrosinebinding (PTB) domain, interacts with the lipoprotein receptor-related protein 1 (LRP1) to reduce the insulin sensitivity of adipocyte. Considering the role of LRP1 in lipid metabolism, we investigated the effect of PID1 on the content and biological activities of serum lipoproteins in pigs. PID1-transgenic pigs were genetated by sperm and magnetic nanoparticles-mediated method. The levels of PID1 in PID1-transgenic pig's liver were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Hence, our results point more precisely towards a function of ARNT2 and TSPYL5 in the early steps of cholesterol synthesis where Lan is formed from Sq. Similarly, previous studies have linked PID1 (Chr 15) to HDL-C level 44 and PEX2 (Chr 4) to levels of HDL-C and TC 45 , whereas the tentative associations in the present study point more precisely towards a function of these loci in the KRPW for cholesterol biosynthesis because the two loci are associated specifically with Lat levels. On the other hand, the associations between Des levels and the two genes ARV1 (Chr 14) and ACSL1 (Chr 15) identify functions of these loci in the BPW of cholesterol biosynthesis.…”
Section: Resultssupporting
confidence: 80%
“…Hence, our results point more precisely towards a function of ARNT2 and TSPYL5 in the early steps of cholesterol synthesis where Lan is formed from Sq. Similarly, previous studies have linked PID1 (Chr 15) to HDL-C level 44 and PEX2 (Chr 4) to levels of HDL-C and TC 45 , whereas the tentative associations in the present study point more precisely towards a function of these loci in the KRPW for cholesterol biosynthesis because the two loci are associated specifically with Lat levels. On the other hand, the associations between Des levels and the two genes ARV1 (Chr 14) and ACSL1 (Chr 15) identify functions of these loci in the BPW of cholesterol biosynthesis.…”
Section: Resultssupporting
confidence: 80%
“…The existing literature has observed similar phenomena in other populations. As the main component of metabolic syndrome, obesity was often accompanied by dyslipidemia [ 36 , 37 , 38 , 39 , 40 , 41 ]. At the same time, studies have shown that adult dyslipidemia was directly related to the increase in BMI [ 9 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four genes previously reported in the literature with an additive genetic effect on precocity were found on Chr2. The PID1 gene has been identified in transgenic pigs, showing higher expression in obese animals [ 69 ], in which PID1 overexpression resulted in the reduction in serum HDL-cholesterol and apolipoprotein A1 levels. The role of the PID1 gene in human lipid metabolism is well known because this gene acts by reducing the sensitivity of adipocytes to insulin mediated by the interaction of domain 1 of phosphotyrosine with the lipoprotein receptor [ 70 ].…”
Section: Discussionmentioning
confidence: 99%